STEREOTIP BUDAYA ANTARMAHASISWA DI LINGKUNGAN FAKULTAS DAKWAH - nurkhalis, nurkhalis; Hasanah, Muizatun (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Cultural differences are often a factor in the occurrence of the conflict and even lead to conflictin society. This study aims to find out what kind of cultural stereotype developed among facultystudents of Da'wah and Communication UIN Ar-Raniry. The approach in this study usingqualitative descriptive. Meanwhile, on data collection techniques in In-depth Interview (throughPurposive Sampling technique) and Documentation. From this research, it is found that thestereotif of the growing culture among students is: The Pidies are Krièt, South Aceh Blacktulledpeople, the Great Beeho people and Gayo people are closed. Although the understandingof students who have studied intercultural communication has begun to open, but the use ofsome stereotypes is still common in the process of daily communication. This is due to socialenvironmental factors that influence the development of a stereotype.Keywords: Cultural, Stereotype, Students, Communication, Environment